Potensi Pengembangan Elektronik Warung Gotong Royong (e-Warong) KUBE PKH Sebagai Alternatif Penanggulangan Kemiskinan di Provinsi Sulawesi Tenggara - Raemon Raemon; Akhmad Marhadi (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2017)
This study aims to describe the potential development of Electronic Program of Warung Gotong Royong (Warong) KUBE PKH in Southeast Sulawesi Province. This research was conducted by using qualitative descriptive method. Data collection techniques were done through observation and in-depth interview. The results showed that in the province of Southeast Sulawesi has been formed 25 units e-Warong KUBE PKH consisting of 13 units e-Warong KUBE PKH in Kendari City and 12 units e-Warong KUBE PKH in Bau-Bau. The potential of e-Warong development can be done through several ways, included: the utilization of skills of KUBE members integrated with KUBE Production; b) e-Warong's integration into a Savings and Loans Cooperative; c) act as a bank agent; d) e-Warong provides cheap food for the general public both in cash and non-cash; e) e-Warong is actively involved in the implementation of an inclusive financial system to all KPM Social Assistance through savings movements that can be derived from social assistance funds; f) e-Warong also has the potential to become a supplier for the type of food-based businesses around the e-Warong management environment (restaurants, catering businesses, pastry vendors, etc.); g) e-Warong also has the opportunity to be developed as a bank agent to attract customers, as well as provide electricity / token payment services, PDAM water in urban areas, internet; h) e-Warong managers in Southeast Sulawesi may also avail the SMS or telephone booking system; i) e-Warong can also be developed as a 3 kg LPG gas distributor and other subsidy products that are needed by the poor, at a very affordable price; and j) The development effort must also be supported by the ability to prepare the financial condition report (balance sheet). keywords: potential, development, e-Warong KUBE PKH, poverty